2003
DOI: 10.1192/bjp.182.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Nithsdale Schizophrenia Surveys 24: sexual dysfunction

Abstract: People with schizophrenia report much higher rates of sexual dysfunction than do the general population. Men and women with schizophrenia have a different pattern of sexual dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
95
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(120 citation statements)
references
References 16 publications
16
95
0
8
Order By: Relevance
“…Although 5AR inhibitors have been generally shown to have few untoward effects and to be well tolerated by patient, they have been shown to sporadically induce erectile dysfunction and gynecomastia (Wilton et al, 1996), which may in turn limit the medication compliance. Nevertheless, it is important to emphasize that these side effects are reportedly rare (Wilton et al, 1996;Wessells et al, 2003) and are also triggered by antipsychotic agents (Segraves, 1989;Macdonald et al, 2003).…”
Section: -A-reductase Inhibitors In Models Of Psychosis M Bortolato mentioning
confidence: 99%
“…Although 5AR inhibitors have been generally shown to have few untoward effects and to be well tolerated by patient, they have been shown to sporadically induce erectile dysfunction and gynecomastia (Wilton et al, 1996), which may in turn limit the medication compliance. Nevertheless, it is important to emphasize that these side effects are reportedly rare (Wilton et al, 1996;Wessells et al, 2003) and are also triggered by antipsychotic agents (Segraves, 1989;Macdonald et al, 2003).…”
Section: -A-reductase Inhibitors In Models Of Psychosis M Bortolato mentioning
confidence: 99%
“…Common shortcomings of existing studies are the lack of a control group or the neglect of gender-specific aspects [4]. An issue of particular concern, however, is the reliability of the assessment instrument since low reliability impairs the power and the validity of a study [7].…”
Section: Discussionmentioning
confidence: 99%
“…Macdonald et al [4] comparing sexual functioning between schizophrenic patients and a population-based sample presented a self-completed genderspecific ''Sexual Behaviour Questionnaire'' (SBQ) covering desire, arousal, performance, and satisfaction. It showed striking face-validity and high clinical utility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Shader and Grinspoon, 1967). A recent survey showed that at least one symptom of sexual dysfunction was reported by 82% of men and 96% of women who had a diagnosis of schizophrenia (MacDonald, 2003).…”
Section: Introductionmentioning
confidence: 99%